The metabolites of vitamin D: role in the diagnosis and in the therapy of vitamin-D-dependent pathologies - O. A. Gromova; I. Yu. Torshin; A. V. Gilels; T. R. Grishina; I. K. Tomilova (LLC "Publisher OKI", 2016)
Most studies on the relationship between vitamin D and various pathologies use only one of the metabolites of vitamin D-25-hydroxyvitamin D3 (25(OH)D3). Hence, the potential effects associated with changes in the levels of other vitamin D metabolites remain outside of the focus of most researchers. In this paper we analyze the known biotransformations of cholecalciferol, possible errors in the assessment of D deficiency related to the properties of various metabolites of vitamin D3, a fundamental biologicaL roLe of the different metabolites of vitamin D3, and prospects for the use of the determination of vitamin D3 metabolite levels for clinical diagnostics.